Implementation of GeoGebra Web in Geometry Learning to Improve Students' Understanding of Hybrid-Based Concepts - Hendry Hendry; Supiyandi Supiyandi; Dafrid Cahyadi Arifin; Yaya Sudarya Triana; Sri Hariyati Fitriasih (LKP KARYA PRIMA KURSUS, 2026)
The limited conceptual understanding of geometry among students remains a significant challenge, particularly due to the lack of interactive learning tools and ineffective integration of digital technology in classroom practices. This community service program aims to implement web-based GeoGebra within a hybrid learning environment to enhance students’ conceptual understanding of geometry. The method employed a participatory and implementation-based approach involving 32 junior high school students and 2 mathematics teachers. The program was conducted through four stages: preliminary study, program design, implementation, and evaluation. Data were collected using pre-test and post-test assessments, questionnaires, and observation sheets. Quantitative analysis was performed using percentage gain and regression analysis, while qualitative data supported behavioral evaluation. The results show a significant improvement in students’ conceptual understanding, with an average score increase from 56.25 to 82.40 and a gain of 65.38%, categorized as moderate-to-high. Furthermore, 81% of students achieved the targeted level of improvement, and student engagement reached 87.6%, exceeding the success indicator threshold. Regression analysis indicated a strong positive relationship (R² = 0.68), suggesting the intervention's effectiveness across different ability levels. In addition, the program positively influenced students’ learning behavior and provided a cost-effective solution by using open-source technology. These findings indicate that integrating GeoGebra into a hybrid learning model is an effective and scalable approach to improving geometry learning outcomes. This program also contributes to the development of sustainable, technology-enhanced educational practices in community service contexts.